Comparison of Trypsin Inhibitors in Preservation Solution for Islet Isolation - Hirofumi Noguchi M.D., Ph.D.; Michiko Ueda; Shuji Hayashi; Naoya Kobayashi; Teru Okitsu; Yasuhiro Iwanaga; Hideo Nagata; Xiaoling Liu; Hiroki Kamiya; Marlon F. Levy; Shinichi Matsumoto (Cell Transplantation, 2009)
Islet transplantation has recently emerged as an effective therapy and potential cure for type 1 diabetes mellitus. Recent reports show that the two-layer method (TLM), which employs oxygenated perfluorochemical (PFC) and University of Wisconsin (UW) solution, is superior to simple cold storage in UW for pancreas preservation in islet transplantation. Moreover, we recently reported that islet yield was significantly higher in the ET-Kyoto solution with ulinastatin (MK)/PFC preservation solution compared with the UW/PFC preservation solution in the porcine model and that the advantages of MK solution are trypsin inhibition and less collagenase inhibition. In this study, we compared ulinastatin with another trypsin inhibitor, Pefabloc, in preservation solution for islet isolation. Islet yield before purification was higher in the MK/PFC group compared with the ET-Kyoto with Pefabloc (PK)/PFC group. The stimulation index was higher for the MK/PFC group than for the PK/PFC group. These data suggest that ET-Kyoto with ulinastatin was the better combination for pancreas preservation than ET-Kyoto with Pefabloc. Based on these data, we now use ET-Kyoto solution with ulinastatin for clinical islet transplantation.